The Influence of Service Quality and Price on Customer Satisfaction of Economy-Type Rooms at Hotel Rajawali in Nanga Pinoh, Melawi Regency - Ferry Kurniawan; Helman Fachri (SAINTIS Publishing, 2025)
This study aims to examine the influence of service quality and price on customer satisfaction of economy-type rooms at Hotel Rajawali in Nanga Pinoh, Melawi Regency. The research is motivated by the importance of service quality and price in shaping customer satisfaction amid increasing competition in the hospitality industry. This study employs a quantitative approach using an associative method. Data were collected through questionnaires distributed to 100 respondents who had stayed at Hotel Rajawali. The variables examined include service quality (X1), price (X2), and customer satisfaction (Y). Data analysis techniques used include multiple linear regression, validity and reliability tests, as well as classical assumption tests such as normality, linearity, and multicollinearity tests. The results of the F-test indicate that service quality and price simultaneously have a significant influence on customer satisfaction. However, the t-test results show that only service quality has a positive and significant partial effect on customer satisfaction, while price does not have a significant effect. These findings suggest that customer satisfaction at Hotel Rajawali is more strongly influenced by service quality rather than price. Therefore, it is recommended that hotel management focus more on improving service quality to maintain and enhance customer satisfaction.